Criminogenic factors associated with youth sex offenders: a qualitative interdisciplinary case study evaluation - Jordaan, Jacques (Acta criminologica, 2018)
The reasons for and onset of sexual offending behaviour are multi-faceted and fluctuate from social (deviant peers), environmental (violent neighbourhood), to personal (psychological detachment) reasons or criminogenic factors. In turn, criminogenic factors are known to determine the likelihood of reoffending behaviour (recidivism) and future dangerousness, but these factors can also direct effective treatment as they are directly linked to the root causes of offending behaviour. Criminogenic factors related to young sex offenders can range from interpersonal deficits, such as deviant sexual interests and arousal patterns, and deviant sexual fantasies, to socialisation practices and personal associations.The aim of this article is to establish the criminogenic factors (causes) associated with the sample-specific youth sex offenders. An interdisciplinary-qualitative approach was followed with eleven youth sex offenders participating in the research endeavour. An in-depth case study analysis was utilised to evaluate the criminogenic factors that played a role in the participants’ sexual offending. The findings of the research suggest that factors such as negative peer influence and peer pressure, exposure to pornography, deviant sexual fantasies, substance abuse, own victimisation and inadequate parenting are significant factors influencing the participants’ deviant sexual behaviours.